Frequency of Low Apgar Score of New Born in Patient Having Abnormal Cardiotocography - Sawaira; Khattak, Sania Tanweer; Akhtar, Nayab; Khan, Uzma; Basir, Wagma (Indus Journal of Bioscience Research, 2025)
Background: Cardiotocography (CTG) is used on a regular basis to check on fetal health, but it remains a topic of investigation for fetal-neonatal outcome correlation and low Apgar scores. Abnormal CTG patterns like fetal tachycardia, fetal bradycardia, and decelerations can signify fetal distress and are correlated with poor neonatal health. Objective: To determine the frequency of Low Apgar score in patient having abnormal cardiotocography. Study Design: Descriptive study. Duration and Place of Study: The study was conducted from March 2023 to September 2023 at the Department of Obstetrics and Gynaecology, Saidu Group of Teaching Hospital Swat. Methodology: 107 pregnant women aged between 18 and 40 with singleton gestations and abnormal CTG were selected using a non-probability consecutive sampling. Demographic data such as maternal age, gestation age, parity and Apgar scores at 5 minutes of delivery were collected. Descriptive statistics and Chi-square tests were employed to associate low Apgar scores (≤5) with demographic parameters with a p-value of ≤0.05 considered to be statistically significant. Results: The mean age of the participants was 28.37 ± 3.08 years, the mean gestational age was 37.11 ± 1.95 weeks, and the mean parity was 1.71 ± 1.47. Of the 107 participants, 76 (71%) had a low Apgar score, while 31 (29%) had a normal score. No significant association was found between low Apgar scores and age, gestational age, or parity (p-values of 0.847, 0.688, and 0.993, respectively). Conclusion: Abnormal CTG is associated with a high frequency of low Apgar scores.